Can an Intraductal Papillary Mucinous Tumor be a Potential Indicator of Concurrent Adenocarcinoma of the Pancreas? - Jarry, Julien; Belleannee, Genevieve; Rault, Alexandre; Sa Cunha, Antonio; Collet, Denis (JOP. Journal of the Pancreas, 2016)
Context Despite the recent progress of diagnostic and therapeutic modalities, survival rates of pancreatic adenocarcinoma remain poor, mainly due to late diagnosis. Case report We report the case of a 56-year-old man who was diagnosed with a symptomatic intraductal papillary mucinous tumor of the pancreas located in the uncus. This tumor was associated with a concurrent stenosis of the isthmic pancreatic duct which resulted in a distal dilation. A Whipple procedure was performed. During the procedure, a concomitant adenocarcinoma was diagnosed 2 cm from the primary intraductal papillary mucinous tumor, causing the isthmic stenosis. A second resection was then performed to the left of the pancreatic isthmus, and adjuvant chemotherapy was performed. The patient is well and without any sign of recurrence 7 months after surgery. Conclusion We discuss the possibility that intraductal papillary mucinous tumors may be a "red flag" enabling earlier diagnosis of a concurrent pancreatic adenocarcinoma arising in another area of the pancreas. Image: Pancreatic ducts lined by tall, columnar, mucin-containing epithelium with papillary projections.